Socioeconomic inequalities in risk of infection with SARS-CoV-2 delta and omicron variants in the UK, 2020-22: analysis of the longitudinal COVID-19 Infection Survey - Martin White; Manish Pareek; Eva J A Morris; Hajira Dambha-Miller; Ben Lacey; Tom Yates; Cameron Razieh; Yogini Chudasama (BMJ Medicine)
Objective To explore the risk of a positive test result for the delta or omicron variant of the SARS-CoV-2 virus in different occupations and deprivation groups in the UK.Design Analysis of the longitudinal COVID-19 Infection Survey.Setting COVID-19 Infection Survey, conducted by the Office for National Statistics and the University of Oxford, UK, a nationwide longitudinal survey to monitor SARS-CoV-2 infection in the community, 26 April 2020 to 31 January 2022.Participants Survey participants recruited from randomly selected households to reflect the UK population (England, Scotland, Wales, and Northern Ireland) were divided into the delta cohort (2 July 2020 to 19 December 2021) and the omicron variant (on or after 20 December 2021), the dominant variants during our study period.Main outcome measures Incidence rate and incidence rate ratio for the presence of the delta and omicron variants by area level deprivation and occupation sector. Multivariable Poisson regression models were fitted to estimate the adjusted incidence rate ratio after adjusting for age, sex, ethnic group, comorbid conditions, urban or rural residence, household size, patient or client facing job, and time (as quarters of the year).Results 329 356 participants were included in the delta cohort and 246 061 in the omicron cohort. The crude incidence rate for the presence of the delta and omicron variants of the SARS-CoV-2 virus were higher in the most deprived group (based on the index of multiple deprivation divided by deciles; delta cohort 4.33 per 1000 person months, 95% confidence interval 4.09 to 4.58; omicron cohort 76.67 per 1000 person months, 71.60 to 82.11) than in the least deprived group (3.18, 3.05 to 3.31 and 54.52, 51.93 to 57.24, respectively); the corresponding adjusted incidence rate ratios were 1.37 (95% confidence interval 1.29 to 1.47) and 1.34 (1.24 to 1.46) during the delta and omicron variant dominant periods, respectively. The adjusted incidence rate ratios for a positive test result in the most deprived group compared with the least deprived group in the delta cohort were 1.59 (95% confidence interval 1.25 to 2.02) and 1.50 (1.19 to 1.87) in the healthcare and manufacturing or construction sectors, respectively. Corresponding values in the omicron cohort were 1.50 (1.15 to 1.95) and 1.43 (1.09 to 1.86) in the healthcare and teaching and education sectors, respectively. Associations between SARS-CoV-2 infection and other employment sectors were not significant or were not tested because of small numbers.Conclusion In this study, the risk of a positive test result for the SARS-CoV-2 virus in the delta and omicron cohorts was higher in the most deprived than in the least deprived group in the healthcare, manufacturing or construction, and teaching and education sectors.